Descriptive and distribution analysis of GitHub repository data - Rao, Dinesh; Dubey, Shishir; Kumar J, Mohan; Rao, Deepak; B, Balaji (International Journal of Engineering and Technology, 2018)
The usage of GitHub by developers is increasing. The organizations are also using GitHub for their project development. As a huge set of users are involved, it leads researchers to analyze the GitHub data. GitHub provides the API (Application programmable interface), to collect its data related to its repository. In our work, the collected data is extensively queried and data is visualized. In this paper, a descriptive analysis is done GitHub data. The results give a lot of insight on the GitHub usage.Â